Comparison of creatinine-based glomerular filtration rate estimation equations in voluntary Indian kidney donors: A single centre study - Shankar Prasad Nagaraju; Kosuru Srinivas; Mohan V Bhojaraja; Srinivas Vinayak Shenoy; Indu Ramachandra Rao; Ravindra Attur Prabhu; Dharshan Rangaswamy; Vasudev Guddattu; Veena Natti Krishna; Megha Nagaraj Nayak (Journal of Nephropharmacology, 2022)
Introduction: In transplantation, accurate estimation of the donor glomerular filtration rate (GFR) is crucial. While various creatinine-based equations are in use, none are validated in Indians. Objectives: This study was conducted to judge the accuracy of creatinine-based GFR estimation equations and urinary creatinine clearance. Patients and Methods: A single-centre, observational and retrospective study at a tertiary care hospital. Adult voluntary donors GFR measured (mGFR) by technetium-99m diethylenetriaminepentaacetic acid (Tc-99m DTPA) were included. The primary outcome was the performance of estimated GFR (eGFR) by "Cockcroft-Gault’s formula corrected for body surface area (CG-BSA) formula", "modification of diet in renal disease (MDRD) 4 and 6 variable equation" and "Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation"; secondary outcome was the performance of "24-hour urinary creatinine clearance (Cr Cl)". Results: 102 kidney donors were analysed with mean age of 45.89 ± 9.98 years and 85.3% females. Mean ± SD mGFR by Tc-99m DTPA was 82.11 ± 14.32 mL/min/1.73 m2 . Mean ± SD eGFR by "CGBSA" was 99.68 ± 23.71 mL/min/1.73 m2 , by "MDRD-4 variable equation" was 98.25 ± 28.61 mL/ min/1.73 m2 , by "MDRD-6 variable equation" was 93.66 ± 19.44 ml/min/1.73 m2 and by "CKD-EPI" was 111.14 ± 31.61 mL/min/1.73 m2 . The lowest bias (2.3), highest precision (16.23), and accuracy (97.1%) were with "MDRD-6 variable equation"; "24-hour urinary Cr Cl" highly overestimated GFR (158.27 mL/min/1.73 m2 ) with the highest bias, lowest precision, and accuracy. Conclusion: The "MDRD-6 variable equation" was the most precise and accurate of the equations, whereas "24-hour urinary Cr Cl" was the least dependable. This study highlights the need for a correction factor or a new GFR estimation equation and not to consider urinary Cr Cl to assess donor GFR.